PERBANDINGAN EFEKTIVITAS PSIKOEDUKASI BOOKLET DAN BLOG TERHADAP PSIKOLOGIS SUAMI SETELAH ISTRI MELAHIRKAN - Mela " Defrianti; Misrawati " "; Erwin " " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract The purpose of this research is to identify comparative effectiveness of pshycoeducation booklet and blog on psychology of husband after wife gave birth  using quasy eksperiment with pre-post test designs with two comparison treatment. Sample of this study were 34 people which divided into 17 people as pshycoeducation booklet group and 17 people as a pshycoeducation blog group based on inclusion criteria using purposive sampling technique. Each group got intervention for a week. This research measured by EPDS. The univariate analysis was conducted to show frequency distribution and bivariate analysis was conducted by Independent sample T-test. The statistic showed p value (0.598) > alpha (0.05) which means that there was no significant differences between effectiveness pshycoeducation booklet and blog on psychology of husband after wife gave birth. This research was recommended collaboration pshycoeducation booklet and blog on psychology of husband after wife gave birth by controlling factors affect psychology of husband. Keyword                                  : Blog, Booklet, Pshycoeducation, Psychology of husband